DISPARITAS PUTUSAN TINDAK PIDANA PENYALAHGUNAAN NARKOTIKA OLEH ANAK DALAM PERSPEKTIF HAM - Elisabeth Adisty Novena; Hari Soeskandi (Gapenas Publisher, 2022)
Narcotics users can be classified in various ways, including as narcotics addicts or victims of narcotics addiction. Naltrexone users and abusers are defined as those who use or abuse narcotics to the point of becoming physically and psychologically dependent on the drugs they use. In accordance with Article 54 of the Narcotics Law, the following things occur: It is specifically stated that